Impact of Obesity on Major Surgical Outcomes in Ovarian Cancer: A Meta-Analysis - Cai, Benshuo; Li, Kang; Li, Gang (Frontiers in Oncology, 2022)
Background The impact of obesity on the surgical outcomes in patients after primary ovarian cancer surgery is unclear. We aimed at conducting a meta-analysis to evaluate the associations between obesity and major surgical outcomes in ovarian cancer patients. Method Embase, PubMed and Web of Science databases were searched for eligible studies. Study-specific relative risks (RR) were pooled using fixed effect model when little evidence of heterogeneity was detected, otherwise random effect model was employed. Results Twelve eligible studies were identified. The pooled incidence rates of all complications were 38% (95%CI: 29%, 47%) for obese patients and 27% (95%CI: 18%, 36%) for nonobese patients. Compared with the non-obese patients, there was a significantly increased risk of all complications in obese patients after ovarian cancer surgery, with a pooled RR of 1.75 (95%CI: 1.26, 2.43). For advanced (stage III-IV) ovarian cancer, the pooled RR of all complications was 1.55 (95%CI: 1.07, 2.24). Obese patients after ovarian cancer surgery were at higher risks of wound complication (pooled RR: 7.06, 95%CI: 3.23, 15.40) and infection (pooled RR: 2.43, 95%CI: 1.51, 3.93) compared with non-obese patients. Such increased risk was not observed for other major complications including venous thromboembolism, ileus and organ failure. Hospital stay days between obese patients and non-obese patients were similar (Standardized Mean Difference: -0.28, 95%CI: -0.75, 0.19). The rates of optimal debulking (pooled RR: 0.97, 95%CI: 0.90, 1.04), readmission/return to operation room (pooled RR: 1.20, 95%CI: 0.56, 2.57) and 30-day mortality (pooled RR: 0.95, 95%CI: 0.54, 1.66) were also comparable between obese patients and non-obese patients. Conclusion Obesity is associated with increased risk of postoperative complications, especially wound complications and infection after primary ovarian cancer surgery. Obesity may not affect their optimal debulking rates and 30-day mortality in patients undergoing ovarian cancer surgery. Besides, to improve surgical outcomes, advanced minimally invasive robotic approach seems to be feasible for the treatment of obese patients with ovarian cancer.